Light Control Design by Using Social Media Telegram Applications Based on Internet Of Things (IOT) - Candra, Rudi Arif; Ilham, Dirja Nur; Hardisal, Hardisal; Sriwahyuni, Sriwahyuni (Politeknik Ganesha Medan, 2019)
Internet of things (IoT) is a concept with the aim of expanding the connectivity of internet network connected to global networks. Internet of Things (IoT) is used to control electronic device that utilizes internet technology to perform control processes such as lamp. This study aims to build control device that utilizes internet technology to carry out the light control process by utilizing social media telegram applications. With NodeMCU V3 as a Digital controller that supports TCP / IP technology. The testing method is carried out using 4 lights and 4 channel relays. The results obtained by the testing process by using commands on the telegram have been successful, the delay time is very dependent on internet connectivity or Wifi.